CB1 receptor localization in rat spinal cord and roots, dorsal root ganglion, and peripheral nerve. - Sanudo-pena M Clara; Strangman Nicole M; Mackie Ken; Walker J Michael; Tsou Kang (Acta Pharmacologica Sinica, 2016)
AIM: The localization of CB1 receptors in the spinal cord, spinal roots, dorsal root ganglion (DRG), and peripheral nerve of the rat was determined. METHODS: We studied the distribution of CB1 cannabinoid receptors by immunohistochemistry using an antibody raised against the N-terminal of the receptor. RESULTS: The spinal cord showed numerous transverse fibers labelled for CB1 receptors throughout and concentrated in the dorsal horn. Lightly-stained cells were observed throughout the spinal cord gray matter. The DRG also showed cells and fibers labelled for CB1 receptors. Labelled fibers were observed in both dorsal and ventral roots as well as in peripheral nerves. CONCLUSION: The presence of CB1 receptors in the DRG, the dorsal root, and the dorsal horn is in accordance with the analgesic effects of cannabinoids. The presence of labelled cells and fibers in the ventral horn and ventral root provides a substrate for cannabinoid-induced muscle relaxant and antispastic effects.